2011
DOI: 10.1016/j.drugalcdep.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Associations among types of impulsivity, substance use problems and Neurexin-3 polymorphisms

Abstract: Background Some of the genetic vulnerability for addiction may be mediated by impulsivity. This study investigated relationships among impulsivity, substance use problems and six neurexin-3 (NRXN3) polymorphisms. Neurexins (NRXNs) are presynaptic transmembrane proteins that play a role in the development and function of synapses. Methods Impulsivity was assessed with the Barratt Impulsiveness Scale Version 11 (BIS-11), the Boredom Proneness Scale (BPS) and the TIME paradigm; alcohol problems with the Michiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Self-reported anxiety symptoms and impulsivity were also examined given their association with SUP (Marmorstein et al, 2010; Petry, 2001; Stoltenberg et al, 2011). Anxiety symptoms were measured using the Beck Anxiety Inventory (BAI; Beck et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported anxiety symptoms and impulsivity were also examined given their association with SUP (Marmorstein et al, 2010; Petry, 2001; Stoltenberg et al, 2011). Anxiety symptoms were measured using the Beck Anxiety Inventory (BAI; Beck et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…They are hypothesized to mediate impulsivity and therefore may be implicated in genetic vulnerability for opioid dependence [92]. In a genome-wide study, Lachman et al [93] found an association between opioid dependence and a wide region of chromosome 14q (exclusive to the Puerto Rican subpopulation) where the NRXN3 gene is located.…”
Section: Genetic Susceptibility To Opioid Dependencementioning
confidence: 99%
“…Specific biological (e.g., genetic) factors may contribute to these gender-related differences (Stoltenberg et al, 2011). Gender-related differences also exist with respect to casual sexual behaviors, observed more frequently amongst men than women (Garcia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%